2020
DOI: 10.3390/nu12072015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Whey Protein Supplementation and Resistance Training on Biomarkers of Vitamin B12 Status: A 1-Year Randomized Intervention in Healthy Older Adults (the CALM Study)

Abstract: We investigated the effect of long-term whey supplementation on biomarkers of B12 status in healthy older adults subjected to different schemes of supplements and exercise. The total study population examined at baseline consisted of 167 healthy older adults (age ≥ 65 year) who were randomized to 1-y intervention with two daily supplements of (1) whey protein (3.1 µg B12/day) (WHEY-ALL), (2) collagen (1.3 µg B12/day) (COLL), or (3) maltodextrin (0.3 µg B12/day) (CARB). WHEY-ALL was comprised of three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
1
0
3
Order By: Relevance
“…Linfoma difuso de células B grandes 366 (83) 109 (86) 42 (68) 215 (85) Linfoma folicular 77 (17) 18 ( 14) 20 (32) 39 (15) Tipo de prueba confirmatoria realizada Aspirado de médula ósea 5 ( de 3L fue RICE (25%), seguido por RDHAP (12.5%), REPOCH (12.5%) y GEMOX (12.5%).…”
Section: Tipos De Linfoma No Hodgkinunclassified
“…Linfoma difuso de células B grandes 366 (83) 109 (86) 42 (68) 215 (85) Linfoma folicular 77 (17) 18 ( 14) 20 (32) 39 (15) Tipo de prueba confirmatoria realizada Aspirado de médula ósea 5 ( de 3L fue RICE (25%), seguido por RDHAP (12.5%), REPOCH (12.5%) y GEMOX (12.5%).…”
Section: Tipos De Linfoma No Hodgkinunclassified
“…31 Otro estudio comparó los biomarcadores del estado de B 12 durante cuatro semanas de administración complementaria con cantidades equivalentes de B 12 en una población india con concentraciones bajas de vitamina B 12 , se administró en cápsulas de vitamina (CN-B 12 ), leche de vaca (HO-B 12 en la dieta) o leche de búfala (HO-B 12 en la dieta), obteniendo como resultado que ambas presentaciones son igualmente eficientes para mejorar los biomarcadores de la deficiencia de B 12 . 32,33…”
Section: Evidencias De La Dieta Y De La Administración Complementariaunclassified
“…Recently, we found that cow milk-derived TC-B 12 complex was more effective at stimulating receptor-mediated passage of B 12 across polarized monolayers of human intestinal epithelial (Caco-2) cells than human TC-B 12 complex (Juul et al, 2019). Clinical studies have shown that 8 wk of daily intake of whey protein isolate improved biomarkers of B 12 status in elderly Australians with subclinical B 12 deficiency and, more recently, long-term daily whey powder intake was shown to reinforce B 12 status in healthy elderly Danes (Dhillon et al, 2017;Greibe et al, 2020). Furthermore, it has been reported that whey powder supplement provided over 4 wk was as efficient as synthetic B 12 vitamin pills in improving biomarkers of B 12 deficiency in lactovegetarians (Naik et al, 2019).…”
Section: Short Communication Geneticsmentioning
confidence: 99%